2012
DOI: 10.1016/j.bbamem.2012.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal property of dihydrodehydrodiconiferyl alcohol 9′-O-β-d-glucoside and its pore-forming action in plasma membrane of Candida albicans

Abstract: The aims of this study wereto investigate the antifungal activity as a bioactive property of dihydrodehydro-diconiferyl alcohol 9'-O-3-D-glucoside (DDDC9G) and the mode of action(s) involved in its effect. Antifungal susceptibility testing showed that DDDC9G possessed potent antifungal activities toward various fungal strains with almost no hemolytic effect. To understand the antifungal mechanism(s) of DDDC9G, we conducted the following experiments in this study using Candida albicans. Fluorescence experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…After entering, PI intercalates between the guanine and the cytosine pair of DNA or with a stoichiometry of one unit dye per 3–5 base pairs. After DNA binding, the red fluorescent color of PI enhances more than 20-fold (Suzuki et al, 1997; Choi et al, 2012). From our study, we showed the distribution of the PI inside the C. tropicalis through the injured plasma membrane, and finally establish the cell membrane active mechanisms of protolichesterinic acid in Candida cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After entering, PI intercalates between the guanine and the cytosine pair of DNA or with a stoichiometry of one unit dye per 3–5 base pairs. After DNA binding, the red fluorescent color of PI enhances more than 20-fold (Suzuki et al, 1997; Choi et al, 2012). From our study, we showed the distribution of the PI inside the C. tropicalis through the injured plasma membrane, and finally establish the cell membrane active mechanisms of protolichesterinic acid in Candida cells.…”
Section: Discussionmentioning
confidence: 99%
“…From our study, we showed the distribution of the PI inside the C. tropicalis through the injured plasma membrane, and finally establish the cell membrane active mechanisms of protolichesterinic acid in Candida cells. Maintaining the cytoplasmic membrane integrity is essential to various important functions of microorganisms, including the formation of gradient and discriminating permeability, cellular energetic, synthesis of various biopolymers, and other key virulence determinants (Choi et al, 2012). In this admiration, any changes in the physical state of the cell membrane induced by protolichesterinic acid may hinder with one or more functions directly or indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…To further elucidate the membrane-active mechanisms, we used calcein-containing GUVs composed of PC/PE/PI/ergosterol (5:4:1:2, wt/wt/wt/wt; ref. 34), which mimic the membranes of C. albicans and were prepared using the electroformation method (15). GUVs have become a useful model for imitating biological membranes (35), and morphological changes in the artificial membrane model allow the study of structural and physical changes occurring during interactions with antimicrobial agents (36).…”
Section: Visualization Of the Fungal Membrane-disruptive Action Of Cumentioning
confidence: 99%
“…Damages at the cell membrane level, measured by propidium iodide uptake, are usually indicators of cell death (Simonin et al, 2007; Choi et al, 2012), but it is also possible that some damaged cells retain the ability to recover after a short incubation (Davey and Hexley, 2011). Propidium iodide may also be used as an indicator of cell leakage, or cell permeability (Piotrowski et al, 2015).…”
Section: Discussionmentioning
confidence: 99%